Collaborative Mobile Money Service Provision: Recommendations for National Issues - Zeinelabdin Karrar, Azza; Abdul Rahman, Azizah (International Journal of Engineering & Technology, 2018)
Recently, the developing countries are considering the development of mobile money ecosystems that supports more inclusive financial systems to overcome the high financial exclusion of their population. Such ecosystems can be enabled by facilitating the collaboration between diverse stakeholders from different sectors: financial, telecommunication, regulatory bodies and IT service providers. This development of mobile money ecosystem emphasized on considering existing issues of main stakeholders’ and their conflicting interests. The aim of this paper is to discuss set of recommendations that can help in resolving national issues when participating in collaborative mobile money ecosystem. The research used the Sudanese national mobile money project as case study. The data collection method was qualitative interpretive interviews with different stakeholders in different sectors in Sudan. The researchers analyzed the collected data using qualitative data analysis approach. The results of the analysis focus on representing the multiple perspectives of stakeholders on each identified government’s issue. The research identified six national issues and the interrelation between these issues. The identified issues are: non utilized huge deposits, accountability of big transactions amount, strict customer registration procedures, unsatisfying batch processing, responsibility of customer management and monitoring international remittances. These findings contribute toward better understanding to the mobile money ecosystem in Sudan from government’s perspective. This understanding can facilitate building successful value propositions between mobile money stakeholders which can results in better financial services.